Urbanization in Southeast Asia : Issues and Impacts - Moe Thuzar; Yap, K. S. (Book collections on Project MUSE., 2012)
Urbanization occurs in tandem with development. Countries in Southeast Asia need to build - individually and collectively - the capacity of their cities and towns to promote economic growth and development, to make urban development more sustainable, to mitigate and adapt to climate change, and to ensure that all groups in society share in the development. This book is a result of a series of regional discussions by experts and practitioners involved in the urban development and planning of their countries. It highlights urbanization issues that have implications for regional - including ASEAN.